EVALUASI STATUS KESUBURAN TANAH PADA LAHAN PERTANIAN BAWANG MERAH DI SULAWESI SELATAN - Fatmawati Nur; Devi Armita (Agros Journal of Agriculture Science, 2023)
Soil fertility is the ability of the soil to provide complete nutrients in optimum conditions for plants. Evaluation of soil fertility status is very important in crop cultivation activities, including shallot cultivation. This study aims to evaluate the status of soil fertility based on the physico-chemical properties of various shallot agricultural land in South Sulawesi, to be precise in three districts which are the centers of shallot production, namely Enrekang, Jeneponto, and Bantaeng Regencies. This research was conducted in March-May 2022 with research stages including taking soil samples at 5 locations and continued with an analysis of the physico-chemical properties of the soil at the Soil, Plant, Fertilizer, Water Laboratory of BPTP South Sulawesi with parameters including soil texture (physical properties) and parameters of soil chemical properties include pH, organic matter content, total phosphorus (P) and potassium (K), CEC, and base saturation (BS). The results obtained show that based on soil physical properties, agricultural land in Bantaeng Regency is the most appropriate land for shallot cultivation compared to the other four locations because it has a sandy loam soil texture. The same thing applies to the chemical properties of the soil, namely agricultural land in Bantaeng Regency has very high soil fertility status based on the parameters of C-organic, P and K-total content and CEC in the very high category and BS value in the high category, while 2 locations in Enrekang Regency is in the low category and agricultural locations in Jeneponto Regency are in the medium and high categoriesINTISARIKesuburan tanah merupakan kemampuan tanah untuk menyediakan unsur hara yang lengkap dalam kondisi optimum bagi tanaman. Evaluasi status kesuburan tanah sangat penting dilakukan dalam kegiatan budidaya tanaman, termasuk budidaya bawang merah. Penelitian ini bertujuan untuk mengevaluasi status kesuburan tanah berdasarkan sifat fisika-kimia tanah berbagai lahan pertanian bawang merah di Sulawesi Selatan tepatnya di tiga kabupaten yang menjadi sentra penghasil bawang merah yaitu Kabupaten Enrekang, Jeneponto, dan Bantaeng. Penelitian ini dilaksanakan pada bulan Maret-Mei 2022 dengan tahapan penelitian meliputi pengambilan sampel tanah pada 5 lokasi dan dilanjutkan dengan analisis sifat fisika-kimia tanah di Laboratorium Tanah, Tanaman, Pupuk, Air BPTP Sulawesi Selatan dengan parameter meliputi tekstur tanah (sifat fisika) dan parameter sifat kimia tanah meliputi pH, kandungan bahan organik, fosfor (P) dan kalium (K) total, KTK, dan kejenuhan basa (KB). Hasil yang diperoleh menunjukkan bahwa berdasarkan sifat fisika tanah, lahan pertanian di Kabupaten Bantaeng merupakan lahan yang paling tepat untuk budidaya bawang merah dibandingkan keempat lokasi lainnya karena memiliki tekstur tanah lempung berpasir. Hal yang sama berlaku untuk sifat kimia tanah, yaitu lahan pertanian di Kabupaten Bantaeng memiliki status kesuburan tanah kategori sangat tinggi berdasarkan parameter kandungan C-organik, P dan K-total serta KTK dengan kategori sangat tinggi dan nilai KB dengan kategori tinggi sedangkan 2 lokasi di Kabupaten Enrekang pada kategori rendah dan pada lokasi pertanian di Kabupaten Jeneponto berada pada kategori sedang dan tinggi.